Hegemony and Identity: The Chicano Hybrid in Francisco X. Alarcón's Snake Poems - George Hartley (Studies in 20th & 21st Century Literature, 2001)
Snake Poems renegotiates power relations between the discourse of Spanish imperialism and Aztec poetic practice. Alarcón's extended poem enacts a process of ethnic, cultural, and spiritual identification through a confrontation between texts—Alarcón's original poems, passages of commentary from the Spanish Inquisitor Hernando Ruíz de Alarcón's treatise on Aztec spells and invocations, and the Aztec spells themselves in the original Náhuatl, the Aztec language. Each of these three layers of text represents a unique and competing people, ideology, and culture, and it is the clash and the hybrid fusion of these distinct discourses that Alarcón the poet stages in Snake Poems. Ironically, Alarcón the Inquisitor's Treatise functions today as a window onto Aztec ritual and belief, despite its original purpose to stamp out such rituals and beliefs. Alarcón the poet turns the Inquisitor's text against itself and thereby reappropriates and recreates the power of Aztec song as an antidote to Anglo-American imperialism. Through the reappropriation of the transformative poetic vision of the Aztecs, the Chicano becomes the embodiment of the Aztec poetic trope of difrasismo, the suspended unity of conqueror and conquered, of violation and renewal, of flower and song.
Keywords: identity; hegemony; chicano/a; Francisco X. Alarcón; snake poems; power; Spanish imperialism; Aztec poetry; Aztecs; identification; Hernando Ruíz de Alarcón; Náhuatl; hybrid; Anglo-American; imperialism; difrasismo